Socialization of Online Business License Production for Micro, Small and Medium Enterprises (MSMEs) in Sidomulyo District - Lita Adeka Sekty; Hasim As'ari (Jurnal Pengabdian Masyarakat, 2023)
Purpose: The primary aim of the research paper should be explicitly stated to provide a clear understanding of the purpose and direction of the study. Identify the problem or issue under investigation and explain the significance of the research within a particular discipline or sector. Method: Summarize the study's research methodology. Briefly describe the research design, data collection methods, and any analytical techniques or instruments applied to the data analysis. Practical Applications: Examine the pragmatic consequences or uses of the research results. Emphasize the practical applications of the findings in various real-world scenarios, industries, or specific contexts, and outline any potential advantages or enhancements that can be attained. Conclusion: Provide a concise summary of the primary findings derived from the study. Emphasize the importance of the results and their contribution to a broader comprehension of the topic or resolution of the research issue outlined in the introductory section.